The sub-structural synthesis method (ssm) on a heat conduction problem (2007)
In this paper, the application of the Substructural Synthesis Method (SSM) on an engineering problem is presented, based on the theory by Rayleigh-Ritz. This problem is the unidimensional heat conduction analysis on bidimensional systems made of unidimensional members. For this heat conduction problem the associated eigenvalues and their convergence are obtained. Solutions obtained with the SSM are compared to those associated to the h version of the conventional Finite Element Method (FEM). The results obtain opened a whole new panorama of investigation related with determinate the influence on the order of differential equations that ruled the problem about the precision and velocity of the convergence of the solution given by the approximation functions.